Response of andropogon grass to P fertilizers and lime in a Dark-Red Latosol of the cerrados - Couto, Walter; Leite, Gilberto Gonçalves; Sanzonowicz, Claudio (Pesquisa Agropecuaria Brasileira, 1991)
This study intended to determine (i) the amount of P required for the establishment of andropogon grass (Andropogon gayanus Kunth) in an acid soil; (ii) the effect of moderate amount of lime on the response to P; (iii) the relative efficiency of a low reactivity of rock phosphate (RP) and (iv) the effect of the rate of P applied at establishment on the response to annual refertilization rates. The effect of P applied at establishment, from two P sources and three annual refertilization rates were investigated at two lime levels in a virgin clayey Haplustox. Lime reduced the amount of P needed to produce 2000 kg/ha of forage dry matter yield from 180 to 78 P kg/ha-1. Forage yield obtained with a rock phosphate RP improved on time reaching similar yield than with same level of P applied as triple superphosphate (TSP) in the fourth year. Initial P rates of 52 P kg/ha-1 applied as TSP were high enough when lime was also applied. Higher P rates improved first and second year productivity only. Check plots receiving 13 or 26 P kg/ha-1 annually produced more forage yield by the third year than plots receiving highest initial P rate.